2012
DOI: 10.1080/14615517.2012.668075
|View full text |Cite
|
Sign up to set email alerts
|

Trends in consultation and public participation within environmental impact assessment in Kenya

Abstract: The objective of this study was to document trends in public participation within environmental impact assessment (EIA) in Kenya, using a Consultation and Public Participation Index (CPPI) developed for the analysis of EIA Study Reports submitted to the Environment Authority between 2002 and 2010. Results indicated that public participation remained relatively low, with the highest score of 1.65 in 2010, out of a possible score of 5. Scores for individual dimensions within the index fluctuated during the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The practice is not context oriented as cultural, social, economic and political dimensions are mostly ignored nor is it credible and rigorous as facilitators are interested parties and hence not neutral. Similar findings have been document in previous studies including Okello et al [21] who concluded that public participation in Kenya's EIA process "is poor, particularly during the scoping, report review and follow-up stages" [8], who states that public participation within EIA process in Kenya is relatively low [32], who states that public participation in Kenya's EIA process is inadequate [33], who states that project "developers do not usually favour public participation, because they do not see the positive side of this process as a result, they are likely to hide information, or not clearly state data that may be controversial". Public participation in environmental decision making is both shaped by and, in many cases, constrained by the ways in which environmental issues, problems, and solutions are defined or framed through the strategic communication practices of the participants [34].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The practice is not context oriented as cultural, social, economic and political dimensions are mostly ignored nor is it credible and rigorous as facilitators are interested parties and hence not neutral. Similar findings have been document in previous studies including Okello et al [21] who concluded that public participation in Kenya's EIA process "is poor, particularly during the scoping, report review and follow-up stages" [8], who states that public participation within EIA process in Kenya is relatively low [32], who states that public participation in Kenya's EIA process is inadequate [33], who states that project "developers do not usually favour public participation, because they do not see the positive side of this process as a result, they are likely to hide information, or not clearly state data that may be controversial". Public participation in environmental decision making is both shaped by and, in many cases, constrained by the ways in which environmental issues, problems, and solutions are defined or framed through the strategic communication practices of the participants [34].…”
Section: Resultssupporting
confidence: 90%
“…Secondly, a questionnaire survey among EIA Practitioners and other EIA stakeholders in Kenya's renewable energy sector. The international best practice operating principles of public participation adopted are according to André, et al [15] while the Kenya public participation practice was as in Mwenda et al [8], Mwenda and Kibutu [17], Kibutu and Mwenda [20]. Questionnaire respondents were sampled from licenced EIA practitioners in Kenya in the years 2018 while that for other stakeholders was sampled from the National Environment Management Authority (NEMA) Environmental Officers, the Ministry of Energy and civil society.…”
Section: Methodsmentioning
confidence: 99%
“…A review of international literature suggests abundant scope for improving effectiveness of PH and hence the EIA process (general: Hartley & Wood 2005; general in Kenya: Okello et al 2009 andMwenda et al 2012;in China: Du et al 2010;in Pakistan: Nizami et al 2011;in Western Uganda: Kahangirwe 2011; dike relocation case in the Netherlands: Cuppen et al 2012;in Canada: Sinclair et al 2012;in Nigeria: Silas 2013; gas pipeline and tank farm: Lawal et al 2013). Few studies on PH in Indian EIA have shown that the issues raised are limited to safety issues, new road construction and jobs, with little consideration to environmental impact (Sinclair & Diduck 2000).…”
Section: Ph and Its Challengesmentioning
confidence: 99%
“…Environmental aspects are now embedded in the highest law of the land, including a right to a clean, healthy environment, devolution of resource development to local levels of government, and mandatory environmental assessment, auditing and monitoring (Mwenda et al 2012). These constitutional changes are too new for evaluating SEA practice yet, but a decade of legislative and institutional reforms in the water, forest and wildlife sectors may provide a context for considering transparency, accountability and governance in SEA practice, especially if these contribute to more…”
Section: Transparent Accountable and Good Governancementioning
confidence: 99%